(untitled) (Kriminalističke teme, 2023)
The criminal legislation in Bosnia and Herzegovina contains an impressive number of criminal offenses, among which is the illegal making of secret audio and video recordings, which has recently attracted a lot of public attention. In this paper, we will try to answer the question of whether it is sometimes permissible to make secret audio and video recordings, and if the answer is yes when it is possible. We will seek an answer to that question with the help of research methods of the normative framework, domestic judicial practice, comparative judicial practice, and the practice of the European Court of Human Rights in Strasbourg and its public interest construct. We will also present several decisions of the Constitutional Court of Bosnia and Herzegovina and regular courts in Bosnia and Herzegovina so that we can conclude whether and to what extent the "Strasbourg" standards are respected in the application of the law by the domestic judiciary. We will also compare normative solutions from Bosnia and Herzegovina with the same or similar ones from neighboring countries, specifically the Republic of Croatia and the Republic of Serbia, which inherit the same, Yugoslav legal system, and like Bosnia and Herzegovina are passing (Republic of Serbia) or have largely passed (Republic Croatia) process of harmonizing national legislation with the law of the European Union and the law of the Council of Europe.